A survey on the effects of knowledge management on organizational learning: A case study of technical and vocational training organization - Naser Azad; Esmaeil Mehrabi Majolan; Vahid Peej (Management Science Letters)
This paper presents an empirical investigation to study the effects of knowledge management on organizational learning. The study is held in headquarter of technical and vocational training organization in city of Tehran, Iran. The proposed study measures the effects of concept of management, management, knowledge tools, measurement, change management and knowledge content on organizational learning. The study designs a questionnaire in Likert scale and selects a sample of 313 people randomly from 1680 people who work for this organization in city of Tehran, Iran. Using structural equation modeling, the study has detected a positive and meaningful relationship with knowledge management on organizational learning. In our survey, knowledge content is the most important factor followed by change management.